2016
DOI: 10.3390/atmos7020026
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Climate, Land Use and Vegetation Fire Occurrences in El Salvador

Abstract: Vegetation burning is a global environmental threat that results in local ecological, economic and social impacts but also has large-scale implications for global change. The burning is usually a result of interacting factors such as climate, land use and vegetation type. Despite its importance as a factor shaping ecological, economic and social processes, countries highly vulnerable to climate change in Central America, such as El Salvador, lack an assessment of this complex relationship. In this study we rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
1
18
2
2
Order By: Relevance
“…This result contrasts with other studies that found stronger influences of climate than LULC on fire occurrence when using remote sensors [17,22,50]. An open question remains how different resolution fire data are explained by variables operating at different scales.…”
Section: Forest Ecology and Conservationcontrasting
confidence: 95%
See 3 more Smart Citations
“…This result contrasts with other studies that found stronger influences of climate than LULC on fire occurrence when using remote sensors [17,22,50]. An open question remains how different resolution fire data are explained by variables operating at different scales.…”
Section: Forest Ecology and Conservationcontrasting
confidence: 95%
“…The climatic variables mean daily maximum temperature, mean daily minimum temperature, and mean daily annual precipitation, averaged over the period 2003-2011, were significantly correlated with wildfire occurrence in Puerto Rico. In contrast to other tropical and subtropical countries [22,23], mean annual precipitation was not the most important single influencing factor for fire occurrence. Instead, mean daily minimum temperature and daily thermal amplitude represented by the interaction between temperature maximum and minimum were more determinant for fire occurrence and of special consideration in predicting models.…”
Section: Forest Ecology and Conservationcontrasting
confidence: 78%
See 2 more Smart Citations
“…We only used data with confidence levels over 30 % (nominal and high confidence fires as applied in (Armenteras et al, 2016;Chen et al, 2013a) We standardized fire occurrence by the area in km 2 of the unit of analysis, so we used fire density (number of occurrences per 1000 km 2 ) as a fire variable.…”
Section: Data Sources and Analysesmentioning
confidence: 99%